Successful and unsuccessuful teams characteristics in U-20 women`s soccer world cup 2014 - Barreira, J.; Carvalho, L. (Proceedings of the 2016 International Association of Computer Science in Sport (IACSS) Conference, 2016)
The purpose of this study was to analyze technical and tactical characteristics of successful and unsuccessful teams in U-20 Women`s World Cup 2014. We analyzed all the 32 games that happened in the tournament. For each team we collected total shots, shots on goal, fouls, corner kicks and ball possession per game. We found that winning teams showed greater ratios of goals scored, total shots and shots on goal per match than the losing teams. Winning teams also had greater ball possession. Semi-finalists teams presented higher ratios of goals scored, total shots, shots on goal and corner kicks per match than the non-semi-finalists teams. Our results suggest that successful women`s soccer teams have greater offensive strategies which allow them to create more opportunity to shoot, to shoot on goal and, consequently, to score more goals. This information is valuable for coaches to plan more efficient training programs.